Analisis Gurindam Dua Belas Karya Raja Ali Haji Ditinjau dari Aspek Sintaksis - Zulfadhli, Muhammad; Farokhah, Laely; Abidin, Zaenal (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
Gurindam Dua Belas is an old poem derived from an old manuscript by Raja Ali Haji, which is important to study based on the syntactic aspect. This current study examines the origins of phrases, clauses, and sentences in Gurindam Dua Belas written by Raja Ali Haji. This study analyses Gurindam Dua Belas written by Raja Ali Haji, in terms of syntactic aspects. The qualitative approach was used in this research with a descriptive analysis method. The data source is a written source, namely the text of Gurindam Dua Belas by Raja Ali Haji, which consists of 12 articles. The data collection technique used a documentation study. The research instrument was the researcher himself as the main instrument assisted by recording card of data. Data analysis was carried out through the reduction stage, the data presentation stage, and then drawing conclusions and verification stages. Based on a review of 3 aspects of syntactic studies, namely function, category, and role, the results show that in the functional aspect, the predicate function of Gurindam Dua Belas text is predominantly used in the structure of syntactic analysis compared to other functions. In the category aspect, the dominant array of Gurindam Dua Belas used is the nominal phrase category. The largest use of the syntactic role used in Gurindam Dua Belas by Raja Ali Haji is the role as a verb or action. Based on an analysis of the syntactic form, it is identified that each article has a different sentence structure. The dominant sentences in the 83 stanzas of Gurindam Dua Belas by Raja Ali Haji are compound.